Reaction to state control: The case of the mid-eastern Transvaal 1955-1960 - Schirmer, Stefan (My University, 1991)
The growth of the bureaucracy is, according to Merton et al, "widely recognised as one of the major social trends of our time". In South Africa this trend has been identified by a number of writers, many of whom have focused on the Native Affairs Department (NAD). Dubow has shown how the Native Administration Act of 1927 laid the foundation for the NAD's growing involvement in matters affecting Africans. Yudelman, referring to the bureaucracy as a whole, has identified the revenue generated by gold mining as the element that financed the expanding bureaucracy. Thus, he links significant periods of bureaucratic growth with improvements of the gold price. The overall picture that emerges is a state (particularly the NAD) concerned with control; a concern that, to some extent, manifests itself through the medium of an expanding bureaucracy. However, the relationship between this concern and bureaucratic expansion found its fullest expression when the National Party came to power in 1948. Posel has argued that, in the environment created by the alliances that the National Party represented, the NAD's most immediate and pressing concern was the construction of 'better control"'. The bureaucratic structures that resulted laid the foundations for an unprecedented level of state interference in the lives of South Africans. The effects of this interference are the subject of this paper. Essentially, the new NAD policies were aimed against Africans. In the white farming areas of the mid-eastern Transvaal, the policies attempted to undercut Africans' bargaining position on the farms. However, while this state intervention was partially an attempt to bolster the position of white farmers, these intended beneficiaries were also forced to accept bureaucratic regulation in many spheres of their lives. The establishment of this kind of control often leads to conflict. When the state takes it upon itself to make decisions for the individual, some individuals' interests will be undermined. This occurs for two reasons. Firstly, because the state represents a centralisation of decision making, the resulting decision will be based on the basis of common denominators rather than the variety of interests held by individuals. Secondly, the state has its own agenda which does not always coincide with the interests of the individuals it claims to represent. Thus, the state is often involved in a balancing act between its own interests and those of its constituents. These processes produce what Burnheim has called, "an insidious tyranny of numbers. The state homogenises and atomises social relationships. The horizons and expectations of people contract to the limits of those variations that the system constitutes as practical possibilities." However, this kind of bureaucratic concordance does not establish itself automatically. Resistance by people who perceive that their interests will be best served by acting outside the sphere of the bureaucracy can undermine the efficacy of bureaucratic control. In South Africa, new bureaucratic structures were to be established in areas where Africans had never been inclined to passively accepted any proposed restrictions. The extent of the control which others were able to exercise over them was determined by day to day struggles that had a long history. Particularly, the terms and conditions of labour tenancy were influenced by Africans' ability to use the threat of withdrawing their labour. This ability was predicated on African mobility and the existence of viable alternatives to farm labour. The new bureaucracy threatened to radically undermine those options that still remained for tenants. But, these measures were not implemented unproblematically. Nor were they merely shaped by the intentions of officials and legislators. Instead, the reactions of the people who were the bureaucracy's intended subjects fundamentally affected the effectiveness and the form of the new controls and enabled Africans to sustain labour tenant relations. This paper will concentrate on the reactions of the inhabitants of the mid-eastern Transvaal to the bureaux and boards created by the state. In this way it is hoped that valuable insights into the process of the establishment of the new bureaucracy will be provided. Much has been said about the implications of the labour legislation of the 1950s. However, the actual effect that this legislation had on the rural areas is still an opaque issue. In this paper the danger of accepting legislation without analysing its actual impact will become clear. In the mid-eastern Transvaal, the uneasy relationship between farmers and the bureaucracy, the resistance of labour tenants and the Department of Justice's refusal to give up areas of authority to the NAD, all helped to undermine the effectiveness of the labour bureaux. Similar forces made the implementation of the Labour Tenant Control Boards an even more difficult process.
African Studies Seminar series. Paper presented 27 May 1991. Not to be quoted without the Author's permission
Keywords: Apartheid.; Local government. South Africa. State supervision